Interaction Between Microbiota and Immunity: Molecular Mechanisms, Biological Functions, Diseases, and New Therapeutic Opportunities - Jingjing Zeng; Zimeng He; Guoqing Wang; Yuxin Ma; Feng Zhang (MedComm)
ABSTRACT The microbiota is pivotal for our health. It includes different phyla like Bacteroidetes, Firmicutes, Actinobacteria, Proteobacteria, Fusobacteria, and Verrucomicrobia. The interaction between microbiota and immunity shares a bidirectional relationship. The microbiota helps to stimulate immunity development. The immunity influences microbial composition in turn. This interaction is critical for maintaining homeostasis, preventing pathogen invasion, and regulating the immune system. Furthermore, this symbiotic relationship is crucial for maintaining overall health and preventing various diseases. The microbiota–immune system contributes to immune system maturation, while the immune system selects for beneficial microbiota composition, thus enhancing our immunity. This review summarizes the molecular mechanisms and biological functions of the interaction between microbiota and immunity, offering solid evidence for the role of microbiota in immune regulation. Notably, the review categorizes microbiota according to phyla and explains disease associations, molecular effectors, and functional outcomes about the microbiota–immune system. We also introduced three core molecular mechanisms of the microbiota–immune systems. Moreover, we detail the progression from target discovery to clinical trial design for bacterial and immune‐related diseases. Finally, we propose four therapeutic strategies for diseases.